2006
DOI: 10.1051/0004-6361:20065056
|View full text |Cite
|
Sign up to set email alerts
|

Probing cosmic chemical evolution with gamma-ray bursts: GRB 060206 at z = 4.048

Abstract: Aims. We present early optical spectroscopy of the afterglow of the gamma-ray burst GRB 060206 with the aim of determining the metallicity of the GRB absorber and the physical conditions in the circumburst medium. We also discuss how GRBs may be important complementary probes of cosmic chemical evolution.Methods. Absorption line study of the GRB afterglow spectrum. Results. We determine the redshift of the GRB to be z = 4.04795 ± 0.00020. Based on the measurement of the neutral hydrogen column density from the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 160 publications
(85 citation statements)
references
References 31 publications
(38 reference statements)
4
81
0
Order By: Relevance
“…Those finestructure lines are not found in QSO absorbers, but seem abundant in GRB lines-of-sight (e.g. Vreeswijk et al 2004;Starling et al 2005b;Prochaska et al 2006;Fynbo et al 2006;Kawai et al 2006;Penprase et al 2006). We measured their column densities through Voigt profile fitting, which is complicated by the blending of the lines of different velocity systems; for every velocity component, however, a diagnostic set of absorption lines can be measured.…”
Section: Discussionmentioning
confidence: 98%
“…Those finestructure lines are not found in QSO absorbers, but seem abundant in GRB lines-of-sight (e.g. Vreeswijk et al 2004;Starling et al 2005b;Prochaska et al 2006;Fynbo et al 2006;Kawai et al 2006;Penprase et al 2006). We measured their column densities through Voigt profile fitting, which is complicated by the blending of the lines of different velocity systems; for every velocity component, however, a diagnostic set of absorption lines can be measured.…”
Section: Discussionmentioning
confidence: 98%
“…RAPTOR started observations 48.1 minutes after trigger and reported that, after an initial fading, the AG rebrightened 1 hr after burst by ∼1 mag within a couple of minutes (Wozniak et al 2006). Many observatories followed the bright optical AG (Monfardini et al 2006;Stanek et al 2007, and references therein), and Fynbo (2006) carried out spectral observations to determine its large redshift, z = 4.05, later confirmed by other groups. The RAPTOR data clearly show that the rebrightening was due to two flares (Wozniak et al 2006).…”
Section: Grbs With Large X-ray Flares During the Early X-ray Afterglowmentioning
confidence: 92%
“…Tumlinson et al 2007). Fynbo et al (2006) interpreted an absorption feature of the GRB 060206 afterglow spectrum as a possible H 2 detection. Prochaska et al (2009) and Sheffer et al (2009) report the presence of strong H 2 and CO absorption features in the spectrum of the GRB 080607 afterglow.…”
Section: Dust Content and Moleculesmentioning
confidence: 99%